The Relationship Between Big Five Personality Traits and Psychotic Experience in a Large Non-clinical Youth Sample: The Mediating Role of Emotion Regulation - Shi, Jingyu; Yao, Yuhong; Zhan, Chenyu; Mao, Ziyu; Yin, Fang; Zhao, Xudong (Frontiers in Psychiatry, 2018)
Abstract Objective: Despite a long history of interest in personality traits and psychosis, the association between personality traits and psychotic experiences in general population is not yet well understood. One possible factor which could influence the degree of distress from psychotic experiences is emotion regulation. The purpose of this study was to explore whether the association between personality and psychotic symptoms is already apparent in non-clinical youth, and the mediating role of emotion regulation strategies between personality traits and psychotic experiences. Methods: 3147 college students were surveyed via self-report questionnaires measuring the Five-Factor model of personality, emotion regulation strategies and psychotic experiences. Results: Neuroticism was found to be significantly positively correlated with psychotic experiences, while Extraversion, Openness, Agreeableness and Conscientiousness were found to be significantly negatively correlated. Both of the suppression and reappraisal strategies mediated the relationship between personality traits and psychotic experiences. Conclusion: Our findings suggest that the youth with certain personality traits are more likely to have psychotic experiences. The reappraisal emotion regulation strategy could serve as a protective factor against the distress of psychotic experiences.